Different loneliness types, cognitive function, and brain structure in midlife: Findings from the Framingham Heart Study. (November 2022) - Tao, Qiushan; Akhter-Khan, Samia C.; Ang, Ting Fang Alvin; DeCarli, Charles; Alosco, Michael L.; Mez, Jesse; Killiany, Ronald; Devine, Sherral; Rokach, Ami; Itchapurapu, Indira Swetha; Zhang, Xiaoling; Lunetta, Kathryn L.; et al.
Summary: Background: It remains unclear whether persistent loneliness is related to brain structures that are associated with cognitive decline and development of Alzheimer's disease (AD). This study aimed to investigate the relationships between different loneliness types, cognitive functioning, and regional brain volumes. Methods: Loneliness was measured longitudinally, using the item from the Center for Epidemiologic Studies Depression Scale in the Framingham Heart Study, Generation 3, with participants' average age of 46·3 ± 8·6 years. Robust regression models tested the association between different loneliness types with longitudinal neuropsychological performance ( n = 2, 609) and regional magnetic resonance imaging brain data ( n = 1, 829) (2002-2019). Results were stratified for sex, depression, and Apolipoprotein E4 ( ApoE 4). Findings: Persistent loneliness, but not transient loneliness, was strongly associated with cognitive decline, especially memory and executive function. Persistent loneliness was negatively associated with temporal lobe volume ( β  = −0.18, 95%CI [−0.32, −0.04], P  = 0·01). Among women, persistent loneliness was associated with smaller frontal lobe ( β  = −0.19, 95%CI [−0.38, −0.01], P  = 0·04), temporal lobe ( β  = −0.20, 95%CI [−0.37, −0.03], P  = 0·02), and hippocampus volumes ( β  = −0.23, 95%CI [−0.40, −0.06], P  = 0·007), and larger lateral ventricle volume ( β  = 0.15, 95%CI [0.02, 0.28], P  = 0·03). The higher cumulative loneliness scores across three exams, the smaller parietal, temporal, and hippocampus volumes and larger lateral ventricle were evident, especially in the presence of ApoE 4. Interpretation: Persistent loneliness in midlife was associated with atrophy in brain regions responsible for memory and executive dysfunction. Interventions to reduce the chronicity of loneliness may mitigate the risk of age-related cognitive decline and AD. Funding: US National Institute on Aging.